2016
DOI: 10.21037/atm.2016.11.56
|View full text |Cite
|
Sign up to set email alerts
|

At the crossroads from bench to bedside: luteolin is a promising pharmacological agent against myocardial ischemia reperfusion injury

Abstract: The study by Bian et al. (1) found that luteolin (Lut) inhibited myocardial ischemia/reperfusion injury (IRI) by decreasing miR-208b-3p and increasing Ets1 expression levels in rats. Cokkinos (2) has written an editorial commentary for this study and considered it to be elegant. However, he also raised several interesting questions about the study. As the members of the investigate team, we would like to discuss these issues with counterparts.The first question is how relevant to the clinical situation are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Luteolin is a widely distributed flavonoid compound that can be found in a variety of plants. A large number of studies have found that luteolin is a potential cardioprotective agent, and it also has many evidences of cardioprotection in epidemiology [24]. β-sitosterol can also be found in a variety of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin is a widely distributed flavonoid compound that can be found in a variety of plants. A large number of studies have found that luteolin is a potential cardioprotective agent, and it also has many evidences of cardioprotection in epidemiology [24]. β-sitosterol can also be found in a variety of plants.…”
Section: Discussionmentioning
confidence: 99%